Observational Study on User Experience of In-Patient and Domicilliary Palliative Care Facilities Provided at Hospices - Jovi, Chin; Abdul Aziz, Aniza Binti (Journal of Techno-Social, 2020)
Palliative care is the field of medical care intended to provide comfort to patients who have chronic or terminal disease from the time of diagnosis and throughout the course of the illness. MOH (Ministry of Health) has aimed to establish palliative care units for inpatient and outpatient facilities However, there is no design guidelines for hospice centre due to palliative care is still considered a new field in Malaysia. This study reviews the patients’ perception in hospices in Malaysia based on layout, nature, privacy and social support. As a participatory volunteer of the hospices, this case study is carried out with qualitative observations and interviews on two chosen hospices as case study based on their typology, namely Pure Lotus Hospice, an in-patient facility in Penang and Assisi Palliative Care, a domicilliary facility in Petaling Jaya. The finding shows that there is a strong correlation of user perception to the privacy provided in the hospice. This study infers planning for privacy should be a priority when planning for future hospices as well as policies.